Criticality of the random-site Ising model: Metropolis, Swendsen-Wang and Wolff Monte Carlo algorithms - Ivaneyko, D.; Ilnytskyi, J.; Berche, B.; Holovatch, Yu. (Condensed Matter Physics, 2005)
We apply numerical simulations to study of the criticality of the 3D Ising model with random site quenched dilution. The emphasis is given to the issues not being discussed in detail before. In particular, we attempt a comparison of different Monte Carlo techniques, discussing regions of their applicability and advantages/disadvantages depending on the aim of a particular simulation set. Moreover, besides evaluation of the critical indices we estimate the universal ratio Γ⁺/Γ⁻ for the magnetic susceptibility critical amplitudes. Our estimate Γ⁺/Γ⁻− = 1.67±0.15 is in a good agreement with the recent MC analysis of the random-bond Ising model giving further support that both random-site and random-bond dilutions lead to the same universality class.